(3GdEMGWI aj JGQjN ZQfGWIs - (3eMeO Hf YHO Gddg Hf SYjO GdSdeGfj GddhTj GdCUd, GdZQfGWj GdCfOdSj, CHh YHO Gddg, GdTgjQ HdSGf GdOjf GHf GdNWjH,J (B776 (3g` s
(3ChdgG (B:s
(3eHJhQ ChdgG, HeG bHd JQLeI eMeO Hf jMji, Hf YHOGdQMef Hf CMeO Hf YHOGdQMef GdCTYQi ef Cgd bQWHI s
(3BNQgG (B:s
(3CKfGA JQLeI eMeO Hf jMji Hf eMeO Hf jMji GdCTYQi GdeGdbj GdMeO ddg GdPi Ndb GdEfSGf ef eGA UZjQ, hLYdg HTQkG ShjkG HYO Cf cGf aj bQGQg cHjQ HJQLeI YHOGdhgGH Hf YeQ Hf eMeO Hf CHj HcQ GdCSYO Sgd eMeO Hf YHOGdQMef GdMeRGhi s
(3Vef eLehY s
(3bWYI efgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B235s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B262 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B372 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B18 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3GdJGQjNs